The identity category: a product and/or a process - Ciepiela, Kamila (Categories and Units in Language and Linguistics, 2020)
The article focuses on the category of identity and aims to compare and contrast in a cursory manner two major approaches to the issue, namely the one that views identity as a product of the rational mind and the other that expands it to embrace the socio-cultural and interactional milieu. The former sees identity as a category that is constructed as any other object category. The latter posits to move identity to exteriority where it is not only embodied but also negotiated and performed. By drawing on works from the two traditions, the article aims to provide a clearer picture of how the views on the identity construct have changed and developed, by which a conceptually clearer and richer understanding of the issue could have been achieved.